The Causes and Effects of the 1981 Hospital Strike in Ontario: Fiscal Crisis, Changing Labour Process and the Role of Gender in Public Sector Conflict - White, Patrick Jerry (My University, 1988)
In 1981 the Canadian Union of Public Employees (CUPE) staged a strike in Ontario Hospitals. This dissertation is an exploratory case study of the causes and effects of that strike. The dissertation employs elements of the labour process theory to evaluate the hospital worker's action and in so doing provides an opportunity to contribute to the on-going debate concerning this theory. The study is centred on the hospitals of Greater Hamilton and Burlington Ontario. It assesses the role of political environment, union structure and action, and gender in creating and sustaining the conditions for strike action in the public sector.
The economic and political situation leading to the strike is analyzed with a view to understanding how the fiscal crisis in Canada led to the strike. Labour legislation and the fiscal policies of the federal and provincial governments had an impact on hospitals and their workers. Labour legislation in the hospital sector destroyed collective bargaining at a time when changes unpopular with the workers were taking place in the hospital. This encouraged the decision to strike.
The majority of hospital workers in 1981 were women. The dissertation explores, through interviews and archival data, a possible link between gender and the decision to strike. Some changes in the organization of hospital work broke an important care-giving link between women workers and patients.
The repercussions of the strike include charges for the union, for women, and the wider political consequences such as the further undermining of the Hospital Labour Disputes Arbitration Act.
The dissertation concludes that the strike was caused by labour process changes made by management faced with government cost cutting measures. These changes were particularly upsetting to the majority of workers who were women. The illegality of the strike did not deter the decision to strike because the government labour legislation had destroyed the 'normal' bargaining process. Therefore workers felt that there was no real choice but to strike.
Keywords: Sociology; Sociology